2019
DOI: 10.1002/jor.24223
|View full text |Cite
|
Sign up to set email alerts
|

Forefoot and hindfoot kinematics in subjects with medial tibial stress syndrome during walking and running

Abstract: Excessive foot pronation during static standing, walking and running has been reported as a contributing factor for the development of medial tibial stress syndrome (MTSS). The motion of foot pronation consists of hindfoot and forefoot motion. However, no previous studies have investigated forefoot and hindfoot kinematics during walking and running in subjects with MTSS. The current study sought to compare hindfoot and forefoot kinematics between subjects with and without MTSS while walking and running. Eleven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…A previous study 21 found that the midfoot eversion was comparable in magnitude to rearfoot eversion in the first half of the stance phase, suggesting that the midfoot plays an important role in shock attenuation during the absorption phase (i.e., braking phase) in running. Another study 22 exhibited increased forefoot motion during running in patients with MTSS, which is associated with flatfoot; this study suggested the importance of focusing on forefoot kinematics during running. Considering these findings, the rearfoot, midfoot, and forefoot kinematics of flatfoot during running are likely to differ compared with the normal foot.…”
Section: Introductionmentioning
confidence: 63%
“…A previous study 21 found that the midfoot eversion was comparable in magnitude to rearfoot eversion in the first half of the stance phase, suggesting that the midfoot plays an important role in shock attenuation during the absorption phase (i.e., braking phase) in running. Another study 22 exhibited increased forefoot motion during running in patients with MTSS, which is associated with flatfoot; this study suggested the importance of focusing on forefoot kinematics during running. Considering these findings, the rearfoot, midfoot, and forefoot kinematics of flatfoot during running are likely to differ compared with the normal foot.…”
Section: Introductionmentioning
confidence: 63%
“…The development of running injuries is multifactorial, with passive range of motion, muscle strength, biomechanics of the running, gender and body weight [1] [2,3] [4]. During running, muscle stiffness due to malalignment and overuse increases mechanical stress at the insertion of the skeletal muscles to the bone.…”
Section: Resultsmentioning
confidence: 99%
“…Relative 3D rotations between the proximal and distal segments were calculated to quantify the segment angle. Because abnormal kinematics of the rearfoot and midfoot are commonly reported as risk factors for lower limb injuries (Becker et al, 2017(Becker et al, , 2018Hamstra-Wright et al, 2015;Okunuki et al, 2019), the rearfoot and midfoot motion were assessed. Also, since motion in the transverse plane is relatively small, sagittal and coronal plane motions were calculated.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, abnormal foot kinematics is considered as a major risk factor for sports related overuse injuries of the lower limb. Navicular drop, which is an indicator of midfoot pronation (Reshef & Guelich, 2012), prolonged rearfoot eversion, and hindfoot and forefoot eversion and abduction have been reported to related to medical tibial stress syndrome and Achilles tendinopathy (Becker et al, 2017(Becker et al, , 2018Hamstra-Wright et al, 2015;Okunuki et al, 2019). Traction force to the periosteum caused by the foot supinator muscles that resists against excessive foot pronation and eversion can be a cause of medial tibial stress syndrome (Franklyn, 2015).…”
Section: Introductionmentioning
confidence: 99%